Thermal Performance of Hollow Fluid-Filled Heat Sinks - John Nuszkowski; David Trosclair; Calla Taylor; Stephen Stagon (Energies)
The increasing power density of electronic devices drives the need for lighter, more compact heat dissipation devices. This research determines whether a hollow heat sink filled with fluid outperforms solid heat sinks for heat dissipation. Research on the integration of a heat spreader, heat pipe, and finned heat sink as a single component is limited. The copper and aluminum heat sinks consisted of a 4 × 4 fin array with a volume of 44.5 × 44.5 × 44.5 mm3. The working fluids were water and acetone with a 50% fill volume for the hollow copper and aluminum heat sinks, respectively. Each was tested at nine operating points (varying applied heats and air velocities). The hollow copper heat sink had similar overall heat sink thermal resistance while the hollow aluminum increased by 8% when compared to the solid copper heat sink, and the hollow heat sinks had a 2–9% lower fin array thermal resistance. The weight was reduced by 82% and the mass-based thermal resistance was 77% lower than the solid copper heat sink for the hollow aluminum heat sink. The considerable decrease in mass without significant loss in thermal resistance demonstrates the potential widespread application across technologies requiring low-weight components. In addition, the hollow heat sink design provides comparable or superior thermal performance to previous flat heat pipe solutions.